The Effect of Methanolic Soy Extract on Heart Tissue Changes in Ovariectomized Rats - Mohammad Reza Nasirzadeh; Alireza Nourazar; Mir Hadi Khayat Nouri; Leila Roshangar (Journal of Ardabil University of Medical Sciences, 2012)
Background & Objectives: Following to estrogen depletion in postmenopausal womens, its cardioprotective effect decreases. Stroke usually occurs in women during the menopause years. Estrogen hormone therapy is still controversial. Epidemiological data suggest that phytoestrogens have a preventive effect on various estrogen-related diseases/symptoms such as menopausal symptoms, cardiovascular diseases. Some studies suggest that genistein as an important component of soy have cardioprotection effects but its role on inflammation and cardiomyocte injury remained to be elucidated. So, this study was goaled to investigate the cardioprotective effect of methanolic soy extract on heart tissue injures.   Method: In this study 40 female rats were randomly allocated into 4 groups: 1) Control (intact animals), 2) sham surgery (without ovarictomy), 3) ovariectomized (ovx), and 4) treatment (ovx and soy gavage) group that received 60mg/kg per day soy extract in drinking water for 28days (4 weeks). At the end of experiments, the rat heart tissue was processed histologically and the sections were stained with hematoxylin and eosin to examine under light microscope. Statistical analysis was performed using the wilcoxon test.   Results: The results showed that ovariectomy significantly increased inflammation and cardiomyocte injury and soy extract significantly promoted heart tissue recovery (p<0.05).   Conclosions: This study indicated that oral administration of soy extract has a positive effect on attenuation of inflammation and myocyte injury in ovariectomized rat.